2002
DOI: 10.1177/026988110201600303
|View full text |Cite
|
Sign up to set email alerts
|

Additional dopamine reuptake inhibition attenuates vigilance impairment induced by serotonin reuptake inhibition in man

Abstract: There is evidence for a specific impairment of human vigilance following enhancement of serotonergic activity by antidepressant drugs. In the present study, we investigated the putative role of serotonergic-dopaminergic interactions in diminished vigilance by comparing the attentional effects of sertraline, a selective serotonin reuptake inhibitor (SSRI) with additional mild dopamine stimulating effects, with those of paroxetine, a SSRI without dopamine activity, using a placebo-controlled, double-blind, three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
62
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 38 publications
9
62
1
Order By: Relevance
“…Siepmann's et al's [2003] research with normal volunteers showed that sertraline does not have either a positive or a negative ef fect on cognition, and so argues against this possibility. Studies by Furlan's et al [2001] and Schmitt et al [2002] also suggested that sertraline improves depression-related cognition.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Siepmann's et al's [2003] research with normal volunteers showed that sertraline does not have either a positive or a negative ef fect on cognition, and so argues against this possibility. Studies by Furlan's et al [2001] and Schmitt et al [2002] also suggested that sertraline improves depression-related cognition.…”
Section: Discussionmentioning
confidence: 98%
“…Tricyclic antidepressants, having very potent antihistaminic and anticholinergic effects, can interfere with cognitive and psychomotor functions [Riedel and van Praag, 1995]. Sertraline, however, has been shown to have no adverse effect on cognition in healthy volunteers [Furlan et al, 2001;Schmitt et al, 2002]. As our study shows an adverse effect on the executive functions of inhibition in depressed subjects, an improvement in these functions during sertraline treatment was probably related to the reduction in blood flow and cerebral glucose metabolism in the frontal regions in the depressive state [Baxter et al, 1989, Bench et al, 1992, Martinot et al, 1990 and to the increase in cerebral glucose metabolism in the frontal regions after 10 weeks of sertraline treatment [Buchsbaum et al, 1997].…”
Section: Discussionmentioning
confidence: 99%
“…Direct effects of 5-HT on vigilance and the conversion of Trp to melatonin may explain the sedative effects of Trp (Cooper et al, 1991;Schmitt et al, 2002). Correlation analyses showed sedation to be positively associated with impaired memory performance.…”
Section: Discussionmentioning
confidence: 99%
“…As an SSRI, sertraline possesses, besides its serotonergic activity, a relatively high affinity for the human dopamine transporter and may also facilitate dopaminergic neurotransmission. Despite its dopaminergic properties being 100-fold lower than its serotonin reuptake blocking properties, it should be mentioned that this dopaminergic activity clearly distinguishes sertraline from all other SSRIs that do not have such activity [14][15][16]31] . Note also that the potency of sertraline for dopamine reuptake blockade is reported to be about one third that of d-amphetamine [14,16] .…”
Section: Discussionmentioning
confidence: 99%